Neighborhood inequality and spatial segregation: An analysis with tax data for 40 Spanish cities. (November 2021) - Martín-Legendre, Juan Ignacio; Castellanos-García, Pablo; Sánchez-Santos, José Manuel
Abstract: In this paper, we analyse the income distributions in 40 Spanish cities at the neighborhood level using tax data for the 2013–2018 period recently published by the national Tax Agency. To accomplish this, we use several inequality indicators, including the Gini coefficient and the Theil index, whose decomposition allows us to examine the level of segregation of the municipalities in the sample in depth. Our results reveal that the period immediately following the last economic crisis was characterized by an increased income concentration at the top of the distribution, which was mainly due to rising differences within the districts of each city, and by an incipient trend towards greater segregation by income level in the cities under analysis. Moreover, there are significant differences in inequality in the urban centres studied that are not necessarily attributable to the size of their population. Finally, over the period under review, the dependence on labour income and the tax burden were further reduced in the wealthiest districts. Highlights: The period from 2013 to 2018 was characterized in Spain by an increased income concentration at the top of the distribution. This trend was mainly due to rising differences within the districts of each city. There is an incipient trend towards greater segregation by income level in the cities under analysis. The differences in inequality in the cities studied are not necessarily attributable to the size of their population. The dependence on labour income and the tax burden were further reduced in the wealthiest districts.